Kinetic Models of the Adsorption of Hexavalent Chromium by Chitosan from Aqueous Solution - JinLong Yan; Guixiang Quan (Adsorption Science & Technology, 2009)
The batch removal of hexavalent chromium from aqueous solution by chitosan under different experimental conditions, such as the pH value and the initial hexavalent chromium ion concentration, was investigated. The adsorption of hexavalent chromium is highly pH-dependent, the results obtained in the present study indicating that the optimum pH for Cr(VI) ion removal was 4.0. The kinetics of the adsorption of Cr(VI) ions by chitosan were evaluated by the pseudo-first-order, pseudo-second-order, Elovich and intra-particle diffusion kinetic models, respectively. The results show that the pseudo-second-order kinetic model gave a good correlation (r 2 = 0.9942) with the experimental data.